Systematic Literature Review: Interpersonal Communication Problems In Hearing Children From Deaf Parents - Setyaningsih, Santi; Utari, Prahastiwi; Satyawan, Ignatius Agung (Universitas Darussalam Gontor collaboration with ISKI (Ikatan Sarjana Ilmu Komunikasi Indo, 2024)
The main problem in families in which there are Deaf parents and Hearing children is the problem of communication, both verbally and in sign language. Hearing children with Deaf parents are able to communicate in two ways, either verbally with non-Deaf people or using sign language with Deaf people. Communication between children and Deaf parents is an important problem in their social and emotional development. This study aims to determine the communication problems that arise between children and Deaf parents. The main focus is to explore the obstacles experienced by children in understanding and conveying messages from their parents who have hearing impairments. This study uses the Systematic Literature Review (SLR) method. Researchers found 127 Scopus articles in a search using Science Direct and with the help of Mendeley and VOSViewer which were then filtered into 18 articles to be analyzed descriptively. The findings show that lack of communication should not be a reason why Deaf parents cannot have access or information about their children. And appreciate that hearing children or Children of Deaf Adults or CODA have different ways of communicating with Deaf parents, the Deaf community and the hearing or non-Deaf community.